2017
DOI: 10.1158/1535-7163.mct-17-0241
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Tie2 Inhibitor Rebastinib Blocks Recruitment and Function of Tie2Hi Macrophages in Breast Cancer and Pancreatic Neuroendocrine Tumors

Abstract: Tumor-infiltrating myeloid cells promote tumor progression by mediating angiogenesis, tumor cell intravasation and metastasis, which can offset the effects of chemotherapy, radiation, and anti-angiogenic therapy. Here, we show that the kinase switch control inhibitor rebastinib inhibits Tie2, a tyrosine kinase receptor expressed on endothelial cells and pro-tumoral Tie2-expressing macrophages in mouse models of metastatic cancer. Rebastinib reduces tumor growth and metastasis in an orthotopic mouse model of me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 77 publications
2
128
1
Order By: Relevance
“…For example, a conditional VEGFA‐KO mouse model of breast carcinoma in which VEGFA expression was specifically deleted in the monocyte/macrophage lineage, results in breast tumors with unaffected TMEM assembly, but impaired VEGF‐dependent vascular wall disruption and cancer cell dissemination. These observations suggest that specific inhibitors targeting TIE2 HIGH macrophages, such as rebastinib, could be potentially used along with chemotherapy to suppress metastatic dissemination and growth, respectively …”
Section: Tumor‐associated Macrophages In Cancer Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a conditional VEGFA‐KO mouse model of breast carcinoma in which VEGFA expression was specifically deleted in the monocyte/macrophage lineage, results in breast tumors with unaffected TMEM assembly, but impaired VEGF‐dependent vascular wall disruption and cancer cell dissemination. These observations suggest that specific inhibitors targeting TIE2 HIGH macrophages, such as rebastinib, could be potentially used along with chemotherapy to suppress metastatic dissemination and growth, respectively …”
Section: Tumor‐associated Macrophages In Cancer Metastasismentioning
confidence: 99%
“…Further IHC/IF analyses on TMEM sites have indicated that each functional TMEM site is composed of a perivascular macrophage expressing high levels of TIE2, VEGFA, and mannose receptor (MRC1), suggesting they could represent a distinct subpopulation of M2 or M2‐like TAMs. TIE2 HIGH VEGFA HIGH MRC1 HIGH macrophages have been intensely studied as they can induce pro‐angiogenic, pro‐metastatic, immunosuppressive, and chemoresistant niches in a context‐dependent manner. For example, using the well‐described MMTV‐PyMT mouse model of breast carcinoma, it was demonstrated that VEGFA secreted by the TIE2 HIGH macrophage on TMEM sites disassembles the underlying vascular junction proteins, zonula occludens‐1 (ZO1) and vascular‐endothelial cadherin (VE‐CAD), exposing a paracellular passage that metastasizing tumor cells use to escape into the circulation .…”
Section: Tumor‐associated Macrophages In Cancer Metastasismentioning
confidence: 99%
“…The mechanisms underlying these intravasation events have been well elucidated [42,54,5759] and can be directly inhibited in vitro and in vivo by blocking their underlying pathways [42,5860]. …”
Section: Hypoxia Motility and Directionality In The Primary Tumormentioning
confidence: 99%
“…For instance, the selective Tie2 inhibitor rebastinib inhibits TMEM function by inhibiting Tie2 on the TMEM macrophage to prevent VEGF-dependent vascular permeability [8]. The use of rebastinib significantly reduces the number of TMEMdependent circulating tumor cells in the blood and the number of disseminating tumor cells in the lungs [3], and significantly increases overall survival of paclitaxeltreated mice [8], suggesting that Tie2 inhibition of TMEM alone could confer reversal of the chemotherapy-induced prometastatic tumor microenvironment [3].…”
Section: George S Karagiannis John S Condeelis and Maja H Oktaymentioning
confidence: 99%
“…For instance, the selective Tie2 inhibitor rebastinib inhibits TMEM function by inhibiting Tie2 on the TMEM macrophage to prevent VEGF-dependent vascular permeability [8]. The use of rebastinib significantly reduces the number of TMEMdependent circulating tumor cells in the blood and the number of disseminating tumor cells in the lungs [3], and significantly increases overall survival of paclitaxeltreated mice [8], suggesting that Tie2 inhibition of TMEM alone could confer reversal of the chemotherapy-induced prometastatic tumor microenvironment [3]. Results similar to that obtained with rebastinib inhibition of chemotherapy-induced prometastatic changes have been phenocopied after genetic ablation of the MENA gene in the MMTV-PyMT mouse model, which spontaneously develops metastatic breast tumors [3], consistent with the finding that increased MENA INV expression is a chemotherapy-induced prometastatic change, critical for cancer cell dissemination [3].…”
Section: George S Karagiannis John S Condeelis and Maja H Oktaymentioning
confidence: 99%